Synthesis of 4-aminoantipyrine derived Schiff bases and their evaluation for antibacterial, cytotoxic and free radical scavenging activity - Shoaib, Mohammad; Rahman, Ghawsur; Ali Shah, Syed Wadood; Umar, Mohammad Naveed (Bangladesh Journal of Pharmacology, 2015)
The work was aimed to synthesize 4-Aminoantipyrine derived Schiff bases in economical way and to screen it for study the effect of nitro group on its antibacterial potential, conduct antitumor preliminary study, the effects of group presence in benzylidene phenyl ring on the cytotoxic potentials and study the effects of electron withdrawing and donating group on antioxidant potential. We used green method with 75% reduction in general synthesis time of Schiff bases. Synthesized compound possess antibacterial potentials and nitro group presence enhances this potential. G2, G3, G4, G5, G6, G7 and G8 have significant cytotoxic and no significant antioxidant activity.